Получение электрокоммутационных слоев керамических теплопереходов методом детонационного напыления - Ashcheulov, A. A.; Dunaenko, A. Kh.; Pundik, V. I.; Romanyuk, I. S.; Fotiy, V. D. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
A technology has been developed for producing electro-commutation layers on ceramic plates of Peltier thermoelectric modules using the method of detonation spraying. The resulting layers are characterized by increased adhesion, low electrical contact resistance, and satisfactory solderability.